Clinical outcomes of tracheoesophageal diversion and laryngotracheal separation for aspiration in patients with severe motor and intellectual disability. (2nd December 2015) - Takano, Kenichi; Kurose, Makoto; Mitsuzawa, Hiroaki; Nagaya, Tomonori; Himi, Tetsuo
Abstract: Conclusions: Tracheoesophageal diversion (TED) and laryngotracheal separation (LTS) can prevent aspiration pneumonia and improve the morbidity of patients with severe motor and intellectual disability (SMID). By improving hospitalization rates and care needs, the quality-of-life can be improved for the patients and their parents. Objectives: This study evaluated the clinical outcomes of TED and LTS in patients with intractable aspiration and SMID. Methods: This study retrospectively reviewed patients with SMID and intractable aspiration pneumonia who underwent TED or LTS at the institution between January 2008 and January 2015. It assessed the frequency of sputum suctioning, the number of pre-operative and post-operative hospitalizations, the operative time, and complications. Results: Forty patients were identified during the study period. After surgery, there were significant reductions in the frequency of secretion suctioning (from 165.0 times/day to 33.0 times/day) and the number of hospitalizations because of aspiration pneumonia (from 5.4 times/year to 0.2 times/year). A tracheocutaneous fistula occurred in one (2.5%) patient, and two (5.4%) patients developed tracheoinnominate artery fistulas. In the latter group, the innominate arteries were successfully ligated and endovascular embolization was performed.